CHALLENGES OF BLOCKCHAIN TO LAW AND STATE - Kubaeva, Ismigul (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This study delves into the challenges of blockchain to law and state, an area of increasing academic and practical significance. By examining blockchain the research aims to provide a nuanced understanding of its implications in law and state. Employing analytical and qualitative methods, the findings highlight the impacts of blockchain, offering contributions to private international law researchers.